Prediction and longitudinal study of CSF biomarkers in mild cognitive impairment - Brys, Miroslaw; Pirraglia, Elizabeth; Rich, Kenneth; Rolstad, Sindre; Mosconi, Lisa; Switalski, Remigiusz; Glodzik-Sobanska, Lidia; De Santi, Susan; Zinkowski, Ray; Mehta, Pankaj; Pratico, Domenico; Saint Louis, Leslie A.; et al. (Neurobiology of aging, 2009)
To longitudinally evaluate five cerebrospinal fluid (CSF) biomarkers in the transition from mild cognitive impairment (MCI) to Alzheimer's disease (AD). A baseline and 2-year follow-up clinical and CSF study of 86 subjects, including 22 MCI patients that declined to AD (MCI-AD), 43 MCI that did not deteriorate (MCI-MCI) and 21 controls (NL-NL). All subjects were studied for total and phosphorylated tau (T-tau, P-tau 231), amyloid beta (Aβ) Aβ 42/Aβ 40 ratio, isoprostane (IP) as well as P-tau 231/Aβ 42/40 and T-tau/Aβ 42/40 ratios. At baseline and at follow-up MCI-AD showed higher levels P-tau 231, T-tau, IP, P-tau 231/Aβ 42/40 and T-tau/Aβ 42/40 ratios and lower Aβ 42/Aβ 40 than MCI-MCI or NL-NL. Baseline P-tau 231 best predicted MCI-AD (80%, p < 0.001) followed in accuracy by P-tau 231/Aβ 42/40 and T-tau/Aβ 42/40 ratios (both 75%, p's < 0.001), T-tau (74%, p < 0.001), Aβ 42/Aβ 40 (69%, p < 0.01), and IP (68%, p < 0.01). Only IP showed longitudinal effects ( p < 0.05). P-tau 231 is the strongest predictor of the decline from MCI to AD. IP levels uniquely show longitudinal progression effects. These results suggest the use of CSF biomarkers in secondary prevention trials.